Cooperativismo como ferramenta para o empoderamento comunitário: o caso da Coopact na Vila de Tracupá, em Tucano-Ba - Mota, Lucas Cauã de Souza (2023)
Empowerment is a polysemic concept that has as its central point the process of increasing the power and autonomy of individuals and groups, which are often oppressed, marginalized, discriminated against and/or socially dominated. The literature suggests that the Popular and Solidarity Economy, especially cooperativism, brings relevant contributions to the empowerment process, collaborating with the construction and strengthening of bonds of trust and solidarity, favoring the protagonism of local actors and projecting their results to the community. In this perspective, in order to understand the possible relationships between the cooperative activity and the empowerment process, a case study was carried out, which aimed to analyze the reflections of the performance and operational context of the Cooperativa dos Produtores de Artefatos de Couro da Comunidade de Tracupá (COOPACT) on the level of empowerment of residents of the village of Tracupá, municipality of Tucano-BA. Documentary analysis and semi-structured interviews with the cooperative manager were used to analyze the actions and operational context of the cooperative, and to assess the level of empowerment of residents of Vila de Tracupá, questionnaires were used based on a set of variables and indicators related to the individual and community empowerment proposed by SOLER (2014) and adapted by HURTADO (2021). The results of the research allowed us to infer that the population of the Tracupá district presented an above-average level of individual and community empowerment in most of the observed variables, with several indications that the cooperative's performance had a positive impact on the empowerment of this community.